An Unusual Cause of Altered Mental Status in Elderly—Acute Cerebellitis: A Case Report and Review. (9th December 2013) - Patel, Priyank; Rayamajhi, Supratik; Tokala, Hemasri; Laird-Fick, Heather
Abstract : Acute cerebellitis is a rare diagnosis found mostly in the pediatric population. The etiology, in most instances, is unknown. We describe the case of a 61-year-old woman who presented with acute mental status changes, signs of cerebellar dysfunction, and MRI findings of acute cerebellitis. A brief review of the existing literature and comparison of our case with previous reports are also presented.